2020
DOI: 10.1017/cem.2019.458
|View full text |Cite
|
Sign up to set email alerts
|

Patient race, ethnicity, and care in the emergency department: A scoping review

Abstract: ObjectivesHealth disparities between racial and ethnic groups have been documented in Canada, the United States, and Australia. Despite evidence that differences in emergency department (ED) care based on patient race and ethnicity exist, there are no comprehensive literature reviews in this area. The objective of this review is to provide an overview of the literature on the impact of patient ethnicity and race on the processes of ED care.MethodsA scoping review was conducted to capture the broad nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 33 publications
0
56
0
Order By: Relevance
“…Healthcare disparities among racial and ethnic minorities have been widely documented. A recent scoping review by Owens et al ., revealed that minority groups had less acute triage scores, longer waiting times and were less likely to receive analgesia 36 . Furthermore, there were increased rates of Left Without Being Seen and Leaving Against Medical Advice among Indigenous minority groups globally 36 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Healthcare disparities among racial and ethnic minorities have been widely documented. A recent scoping review by Owens et al ., revealed that minority groups had less acute triage scores, longer waiting times and were less likely to receive analgesia 36 . Furthermore, there were increased rates of Left Without Being Seen and Leaving Against Medical Advice among Indigenous minority groups globally 36 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent scoping review by Owens et al ., revealed that minority groups had less acute triage scores, longer waiting times and were less likely to receive analgesia 36 . Furthermore, there were increased rates of Left Without Being Seen and Leaving Against Medical Advice among Indigenous minority groups globally 36 . Aboriginal and Torres Strait Islander peoples are two and a half times more likely to have leave events compared to non‐Indigenous Australians 37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences in healthcare systems, especially in availability of health care coverage and personal/individual cost of accessing healthcare, does have the potential to affect which factors influence unscheduled care use by cancer decedents. Furthermore, there are significant population and demographic differences between the USA and other countries, particularly with regards to the association between ethnicity and socioeconomic status 45 , which may have confounded the association between race and unscheduled care use by failing to correct for deprivation 46,47 . Having more studies conducted outwith the USA would be of benefit to improving the relevance of these findings to countries with national health systems.…”
Section: Implications For Research and Practicementioning
confidence: 99%